Onde está a Botânica na alimentação? Uma sequência didática como estratégia de mitigação da Impercepção Botânica - Paixão, Breno Souza (2024)
The main objective of this study was to investigate how a didactic sequence that uses food plants as a practical model can contribute to mitigating Botanical Imperception in ninth grade students. To this end, the formulation of the didactic sequence involved different strategies that, according to the literature on the subject, were present in successful botany teaching experiences. At the end of the formulation process, the sequence was divided into three stages: Diagnostic (whose main objective was to assess the participants' level of Botanical Imperception); Theoretical-Practical (in which the students had contact with the plants); and Evaluative (which aimed to carry out a joint evaluation of the activity). The evaluation of the fulfillment of the objective involved quantitative methodologies (evaluation of the degree of Botanical Imperception of the participants) and qualitative methodologies (content analysis of the students' perceptions after the didactic sequence). After analysis, 3 of the strategies used stood out in terms of meeting the objective: The use of plants that present some curious and unusual fact or plants that undergo industrial processes before being consumed, because these examples arouse the students' interest and help them to become fascinated with plants; Leaving the classroom to carry out the activity; and the use of a digital game in the last stage of the didactic sequence. Finally, it can be concluded that formal education has the power to overcome Botanical Imperception and that the use of innovative didactic sequences is one of the countless tools available for use in this battle.